2015
DOI: 10.1007/s11002-015-9371-0
|View full text |Cite
|
Sign up to set email alerts
|

Loyalty as a matter of principle: the influence of standards of judgment on customer loyalty

Abstract: Ethicists refer to people who make judgments based on normative principles as deontologists. Their ethical standards are such that loyalty is an important characteristic to them-which could make them appealing consumers for marketers to target. In a series of three studies, we illustrate the following: whether deontological standards of judgment positively impact their consumer loyalty, if normative advertising campaigns are more effective for deontologists than for utilitarians, and whether the loyalty pronen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…The first prediction was based on recent debates in the field of moral psychology indicating that people's stronger inclination towards the utilitarian principle that is observed under certain conditions can, but does not have to, imply weaker inclination towards the deontological principle. That is, making decisions in line with the utilitarian principle does not imply that one acts simultaneously in opposition to the deontological principle (Conway & Gawronski, 2013;Greene et al, 2008;Love, Salinas, & Rotman, 2020;Love, Staton, & Rotman, 2015). When interpreting the outcomes of Experiments 1-4, we concluded that our participants were more willing to make utilitarian choices after exposure to market relationships.…”
Section: E Xperimentmentioning
confidence: 77%
“…The first prediction was based on recent debates in the field of moral psychology indicating that people's stronger inclination towards the utilitarian principle that is observed under certain conditions can, but does not have to, imply weaker inclination towards the deontological principle. That is, making decisions in line with the utilitarian principle does not imply that one acts simultaneously in opposition to the deontological principle (Conway & Gawronski, 2013;Greene et al, 2008;Love, Salinas, & Rotman, 2020;Love, Staton, & Rotman, 2015). When interpreting the outcomes of Experiments 1-4, we concluded that our participants were more willing to make utilitarian choices after exposure to market relationships.…”
Section: E Xperimentmentioning
confidence: 77%
“…This may help to explain why, despite demonstrating significant differences in unethical intentions and behaviors across our experimental conditions, the cell means for some of our dependent variables were relatively low in an absolute sense (i.e., below the scale midpoint). Certain consumers may take a deontological view on morality whereby moral rules are black and white, and stealing or cheating is always considered wrong (Love, Staton, & Rotman, ). Conversely, if some consumers are inclined to perceive their unethical treatment of harmful brands as morally justified, then such behaviors should be more likely to emerge among those consumers who are more chronically sensitive to justice violations than among those who are less so (Colquitt, ; Schmitt, Baumert, Gollwitzer, & Maes, ).…”
Section: Discussionmentioning
confidence: 99%
“…Decision‐context factors such amount of purchase planning (extensive vs. spontaneous), the environmental context (public vs. private), or even the cognitive resources available to consumers may enable or diminish consumers' ability to channel PMI to justify and support their ethical actions (Das et al ; Kim et al ). Additionally, future research should investigate whether personal factors such as regulatory focus (Melnyk et al ) or ethical orientation (Love, Staton, and Rotman ) moderate the connection between perceived influence and consumer action.…”
Section: Discussionmentioning
confidence: 99%